Does bank competition spur firm innovation? - Peisen Liu; Houjian Li (Journal of Applied Economics, 2020)
For transition economies, the virtues of financial development for economic growth are obvious; however, bank competition has dubious effects due to various firm characteristics. This study uses Chinese banking and firm data from 1998 to 2011 to examine how bank competition affects firm innovation and how firm size and ownership influence the effects of bank competition. The results show that bank competition promotes firm-level innovation and that this positive effect is stronger for small firms and non-state-owned enterprises (non-SOEs). In addition, bank competition has a more beneficial influence on innovation for transparent firms and domestic firms. These conclusions thus shed light on the real effects of bank competition and the determinants of firm innovation in developing countries.
Keywords: 330; Bank competition; firm innovation; SOE; state-owned commercial bank